Moderní chirurgická a biologická léčba karcinomu prsu - Weinberger, V; Minář, L; Brančíková, D (Ceska gynekologie, 2012)
Breast cancer is the most common cancer of women in the Czech Republic. According to data from the National Cancer Registry (NOR) in 2007, the incidence is 122.7 cases of breast cancer in 100 000 women per year. Czech Republic occupies in the incidence of women breast cancer 26th place in the world and 17th place in Europe. Annually it has been diagnosed 6500 these tumors, 1700-1900 women die for him in the Czech Republic (data from 2007). The incidence show long-term upward trend (an increase of 32% in 2007 compared to 1995), while mortality has long been stabilized. In this favorable outcome involved the introduction of systematic screening of mammography in women over 45 years of age, diagnosis of early stages of disease, effective adjutant therapy and treatment of metastatic disease. In an international comparison of mortality, the Czech Republic belongs to 71th place in the world and the 27th place in Europe. Malignant neoplasm of breast cancer often affects women of working age, nearly 43% of patients are younger than 60 years. Long-term increasing incidence and stable mortality lead to a further increase in prevalence, which in 2007 reached more than 55 000 women living with breast cancer or its history. The various modalities of treatment include surgery, radiotherapy, systemic chemotherapy, hormonal therapy and targeted biological therapy. Fastest-growing issues in breast cancer management is the sentinel nodes and non-invasive breast cancers. This entity was newly assigned and represented by a lobular carcinoma in situ (LCIS) and ductal carcinoma in situ (DCIS). DCIS as noninvasive cancer of the breast is generally 15-20% of breast cancers diagnosed and the number is growing.
Keywords: Sentinel Lymph Node Biopsy; nádory prsu; biopsie sentinelové lymfatické uzliny; cílená molekulární terapie; lidé; Female; Molecular Targeted Therapy; Breast Neoplasms; ženské pohlaví; Humans